Unergatives are different: Two types of transitivity in Samoan. Issue 1 (16th March 2018) - Tollan, Rebecca
Abstract : This paper provides arguments in favour of a non-unified treatment of transitive and unergative verbs, based upon the patterning of unergative constructions in the ergative-absolutive language Samoan. Building upon a proposal by Massam (2009 ; to appear ), I argue that unergative subjects in Samoan are merged lower than transitive subjects, the result being a difference in case marking patterns associated with each verb type. In the spirit of much work which has advocated for a split v P structure (e.g., Pylkkännen 2008 ; Harley 2013 ; Legate 2014 ; a.o.), I propose that unergative subjects are merged in the specifier of v P, while transitive subjects are introduced in a higher projection (VoiceP). This proposal is motivated primarily from split case patterning: while Samoan unergative subjects appear with absolutive case, addition of an object to an unergative verb does not yield the typical ergative-absolutive pattern associated with canonical transitives. Instead, a non-ergative case pattern arises, in which the subject is absolutive, and the object is marked with the prenominal marker i . The Samoan UNERGATIVE + OBJECT construction bears similarities with another set of two-place (so-called MIDDLE VERBS ) which exhibit the same ABS - i case frame. Despite the absence of ergative case, both UNERGATIVE + OBJECT and middle constructions are syntactically transitive with respect to various language-internal diagnostics. I argue that the case split results from differing case assigning properties of v and Voice: i is analysed as structural accusative case, assigned to the object by v 0, while ergative subjects are assigned case by Voice 0 . The division of external arguments across two VP-external projections can be captured by expanding Dowty's (1991 ) framework of thematic proto-roles, whereby unergative and middle "proto- low " ( v P) agents encompass a subset of the semantic properties of full-fledged transitive "proto- high " (VoiceP) agents. The additional properties of proto-high agents correspond to additional phrasal structure.